Evaluasi Pendidikan dalam Praktik Guru: Studi Tentang Penyusunan Instrumen Penilaian di SD Negeri 1 Buahan - I Made Wirya Sudana (UPADHYAYA: JURNAL PENELITIAN PENDIDIKAN, 2026)
This study aims to describe the implementation of educational evaluation in teachers’ practice, particularly focusing on the process of developing assessment instruments at SD Negeri 1 Buahan. The research examines the implementation of learning evaluation, the stages of assessment instrument development, the challenges faced by teachers, and the efforts made to improve the quality of assessment instruments. This study employed a descriptive qualitative research method. The research subjects were classroom teachers at SD Negeri 1 Buahan. Data were collected through in-depth interviews with teachers as the main informants. The collected data were analyzed using descriptive qualitative techniques, including data reduction, categorization, and conclusion drawing. The findings indicate that teachers have implemented educational evaluation continuously through formative and summative evaluations integrated into the learning process. Assessment instruments are developed systematically based on learning objectives and competency achievement indicators. The main challenges encountered by teachers include the heterogeneity of students’ abilities and limited time to design adaptive and fair assessment instruments. To address these challenges, teachers have undertaken several efforts, such as strengthening the analysis of learning objectives, developing assessment instruments collaboratively, utilizing digital learning resources, and conducting continuous review and revision of assessment instruments. The study concludes that educational evaluation designed in a reflective and professional manner plays a significant role in improving the quality of learning and enhancing teachers’ professional competence in elementary schools.